MENGELOLA KONFLIK PEMANFAATAN RUANG BERBASIS NILAI NILAI LOKAL RUANG KOTA KORIDOR JALAN MALIOBORO - KOTA JOGJAKARTA - Edi Purwanto; A Djunaedi; S Sudaryono; B.Hari Wibisono (Diponegoro University, 2012)
Corridor of Malioboro Street has the potential to spatial utilization conflict. Spatial agents think and attempt to build a strategy in order to remain and be able to utilize spaces for activities, but by reducing risks of conflicts as minimum as possible. The question is how is the strategy to manage spatial utilization conflict that they build together? This research applied the approach of phenomenology naturalistic, the research finding shows that the spatial consensus concept built in spatial utilization. The spatial consensus built based on compromises and negotiation has been built in a long period of time. The agreement based on their own initiatives, the representative system was through the community and association boards, and using the third party as facilitator. The substance contained in spatial consensus concept is building the communication to deal with the utilization of space collectively and in the same or different period of time by still prioritizing the principle of togetherness, tolerance, and mutual understanding not to harm others and then called as local values used as the norms and institution to agree with collectively.